2018
DOI: 10.1016/j.molcel.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Pause Sites Delineate Stable Nucleosome-Associated Premature Polyadenylation Suppressed by U1 snRNP

Abstract: Summary Regulation of RNA polymerase II (Pol II) elongation is a critical step in gene regulation. Here, we report that U1 snRNP recognition and transcription pausing at stable nucleosomes are linked through premature polyadenylation signal (PAS) termination. By generating RNA exosome conditional deletion mouse embryonic stem cells, we identified a large class of polyadenylated short transcripts in the sense direction destabilized by the RNA exosome. These PAS termination events are enriched at the first few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 56 publications
(116 reference statements)
4
127
0
Order By: Relevance
“…55 genes showed simultaneously decreased CPA and termination ( Figure S7A). Premature termination in the absence of a detectable polyadenylated product most likely reflects the unstable nature of such transcripts (Chiu et al, 2018). In the reverse scenario, decreased intragenic PAS usage without associated changes in termination possibly reflects the uncoupling of CPA and termination as described in Figure 2.…”
Section: Transcriptional Regulators Are Controlled By Pcf11-dependentmentioning
confidence: 95%
“…55 genes showed simultaneously decreased CPA and termination ( Figure S7A). Premature termination in the absence of a detectable polyadenylated product most likely reflects the unstable nature of such transcripts (Chiu et al, 2018). In the reverse scenario, decreased intragenic PAS usage without associated changes in termination possibly reflects the uncoupling of CPA and termination as described in Figure 2.…”
Section: Transcriptional Regulators Are Controlled By Pcf11-dependentmentioning
confidence: 95%
“…Promoter-proximal transcriptional pausing has recently been linked to premature termination in metazoans (Chiu et al, 2018;Erickson et al, 2018;Krebs et al, 2017;Steurer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in metazoans have suggested that RNA polymerases paused proximally to promoters are targeted for premature termination, with the released RNA undergoing degradation (Chiu et al, 2018;Krebs et al, 2017). To test whether promoter-proximal pausing in yeast is associated with premature termination, we calculated and compared the TR WT and TII Mtr4 for the first 200nt after TSS.…”
Section: The Role Of Ino80 In Transcription Elongation Is Associated mentioning
confidence: 99%
See 2 more Smart Citations